The Necessarily Unfinished Agenda of Pope Francis: Echoing the Call of Christ - Keenan, James F. (Theological studies, 2026)
This article gives an account of the legacy of Pope Francis particularly in his moral teachings and pastoral practices. From the beginning of his reign, he sought to teach as Christ did, welcoming all into the merciful life of the church. I will examine how through his work with the World Popular Movements and the Synods on the family, Francis developed a remarkable responsive listening; it looks then to the work of Laudato Si? and Fratelli Tutti where he leads us to embrace both the earth and all humankind. It concludes on Dilexit Nos and the Synod on Synodality.